Genomewide Association Studies and Human Disease - Hardy, John; Singleton, Andrew (The New England journal of medicine, 2009)
Genomewide association studies have uncovered many genetic variants that confer susceptibility to disease. This article describes the genomewide association study and new approaches that may address some of its limitations. Genomewide association studies have uncovered many genetic variants that confer susceptibility to disease. This article describes the genomewide association study and new approaches that may address some of its limitations. For 20 years, genetic linkage combined with positional cloning has offered a rational and increasingly straightforward route to finding gene mutations that lead to monogenic disease, such as cystic fibrosis and Huntington's disease (see the Glossary). With a few important exceptions, these searches have led to mutations that alter the amino acid sequence of a protein and that enormously increase the risk of disease. During the past few years, genomewide association studies have identified a large number of robust associations between specific chromosomal loci and complex human disease, such as type 2 diabetes and rheumatoid arthritis 1 (Figure 1). This approach . . .